Studi Kekuatan Pressure Vessel Dengan Menggunakan Material SA-106 Grade B dan SA-516-70N - Silvia Uli Arta Lubis; Mufti Fathonah Muvariz; Nurul Fadilah; Naufal Abdurrahman Prasetyo; Sapto Wiratno Satoto; Nidia Yuniarsih (Politeknik Negeri Batam, 2021)
A Pressure Vessel is a container for storing liquid and gas fluid shaped like a cylinder that can produce pressure from outside or inside. Almost all oil and gas industries often use this object to collect and separate water and oil from offshore exploration. This study aims to determine the strength of a Pressure Vessel and determine which is more economical by comparing two types of materials, namely SA-106 Grade B and SA-516-70N, with the same thickness of 12.7 mm. Simulations are carried out on the shell using SolidWorks software to find out the strength of each material. The data used in this study refer to one of the Pressure Vessels from the company with the basic design following ASME section VIII Div.1 standard 2007, document name